The Evolution of the Hebrew Infinitive, Form and Function: A Diachronic Study with Cross-Linguistic Implications - Fox, Andrew Jordan (1984)
Ph.D. diss.; Order No. DA8428513. Cf. DissAbstr 45 (1985) 2857-A.